2013
DOI: 10.1002/cjce.21906
|View full text |Cite
|
Sign up to set email alerts
|

Pumping characterisation of the maxblend impeller for Newtonian and strongly non‐Newtonian fluids

Abstract: This paper examines the pumping mechanisms generated by the Maxblend impeller. Simulation results obtained with the lattice Boltzmann method (LBM) are presented for Newtonian fluids (Re = 2–140) and strongly shear‐thinning fluids (Reg = 0.1–50) obeying the Carreau–Yasuda model with a very small power index (n = 0.05). In the Newtonian case, the pumping numbers predicted by the LBM are shown to compare favourably to those obtained with the finite element (FEM) as well as to experimental data based on the decolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
(153 reference statements)
0
9
0
Order By: Relevance
“…The impeller that we studied has a similar performance to Maxblend TM , which is extensively used in industrial applications related to the mixing of highly viscous fluids. The Maxblend TM constant is in the range of 15-20 (Stobiac et al, 2014, Patel et al, 2011, Fradette et al, 2007. The Paravisc TM impeller is also used in industrial applications dealing with highly viscous fluids, and its constant is significantly higher; it is approximately 30 (Iranshahi et al, 2006).…”
Section: Power Consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impeller that we studied has a similar performance to Maxblend TM , which is extensively used in industrial applications related to the mixing of highly viscous fluids. The Maxblend TM constant is in the range of 15-20 (Stobiac et al, 2014, Patel et al, 2011, Fradette et al, 2007. The Paravisc TM impeller is also used in industrial applications dealing with highly viscous fluids, and its constant is significantly higher; it is approximately 30 (Iranshahi et al, 2006).…”
Section: Power Consumptionmentioning
confidence: 99%
“…A number of studies can be found in the literature concerning these topics (see, for instance, Kazemzadeh et al, 2016, Patel et al, 2015, Stobiac et al, 2014, Pakzad et al, 2013b. These overall parameters, however, do not reveal details of the fluid dynamics and mixing patterns within the mixers, which can only be obtained with detailed flow field measurements.…”
Section: Introductionmentioning
confidence: 99%
“…These geometries are almost universally employed in the blending of complex fluids, as they all possess low power draw in laminar flow. Direct torque measurement has been performed to obtain power curves in laminar flow (Fradette et al, 2007;Zhang et al, 2013;Fontaine et al, 2013), whilst flow measurements have been found using both intrusive methods such as Laser Doppler Anemometry (Jahangiri, 2007) and nonintrusive methods investigating opaque systems (Patel et al, 2014;Ihejirika and Ein-Mozaffari, 2007) and transparent varieties (Stobiac et al, 2014;Chhabra et al, 2007;Shervin et al, 1991). PIV measurements have become prevalent as the method of choice for non-intrusive determination of flow fields, owing to their non-intrusive nature and ease of application.…”
Section: Figure 1: Typical Butterfly Impellermentioning
confidence: 99%
“…Many studies in literature have been performed on the flow in motionless mixers, employing optical methods such as planar laser‐induced fluorescence (PLIF) and particle image velocimetry (PIV) or decolorization measurement techniques , . The application of the reported methods requires both the fluid and the pipelines to be transparent; therefore, they are not implementable for opaque fluids.…”
Section: Introductionmentioning
confidence: 99%